Degraded land: Assessment, impact, restoration, and challenges - Gulshan Kumar Sharma; Dinesh Jinger; I. Rashmi; Manoj Kumar; Nandha Kumar Natrajan; Roomesh Kumar Jena; Raj Kumar; Suresh Kumar; Kavita Kumari; Rajesh Kaushal; Anupam Barh; Trisha Roy; et al. (Journal of Environmental Management, 2026)

Comparison of Hybrid LSTAR-GARCH Model with Conventional Stochastic and Artificial-Intelligence Models to Estimate Monthly Streamflow - Priyanka Sharma; Farshad Fathian; Deepesh Machiwal; S. R. Bhakar; Survey D. Sharma (Water Resources Management, 2024)

In Situ Rainwater Conservation Through Half-Moon Terraces for Sustaining C. registanense in the Indian Thar Desert - Suresh Kumar; J. P. Singh; Deepesh Machiwal; R. N. Kulloli; S. K. Barik (Water Conservation Science and Engineering, 2024)

Rainfall-runoff modeling using HEC-HMS model in an ungauged Himalayan catchment of Himachal Pradesh, India - C Prakasam; Ravindran Saravanan; Deepesh Machiwal; Mukesh Kumar Sharma (Arabian Journal of Geosciences, 2023)

Evaluating homogeneity of monsoon rainfall in Saraswati River basin of Gujarat, India - Deepesh Machiwal; B S Parmar; Sanjay Kumar; Hari Mohan Meena; B S Deora (Journal of Earth System Science, 2021)

Trends and homogeneity of monthly, seasonal, and annual rainfall over arid region of Rajasthan, India - Hari Mohan Meena; Deepesh Machiwal; Priyabrata Santra; Pratap Chandra Moharana; D. V. Singh (Theoretical and Applied Climatology, 2019)

Analysis of trend in temperature and rainfall time series of an Indian arid region: comparative evaluation of salient techniques - Deepesh Machiwal; Ankit Gupta; Madan Kumar Jha; Trupti Kamble (Theoretical and Applied Climatology, 2019)

Evaluating Cost-Effectiveness of Rainwater Harvesting for Irrigation in Arid Climate of Gujarat, India - Deepesh Machiwal; Sanjay Kumar; Devi Dayal (Water Conservation Science and Engineering, 2018)

Spatial modelling of rainfall trends using satellite datasets and geographic information system - Sanjay Kumar; Deepesh Machiwal; Devi Dayal (Hydrological Sciences Journal, 2017)

Long-term rainfall trends and change points in hot and cold arid regions of India - Deepesh Machiwal; Devi Dayal; Sanjay Kumar (Hydrological Sciences Journal, 2017)

Evaluating persistence and identifying trends and abrupt changes in monthly and annual rainfalls of a semi-arid region in Western India - Deepesh Machiwal; Madan Kumar Jha (Theoretical and Applied Climatology, 2017)

Identifying abrupt changes and detecting gradual trends of annual rainfall in an Indian arid region under heightened rainfall rise regime - Deepesh Machiwal; Sanjay Kumar; Devi Dayal; Shamsudheen Mangalassery (International Journal of Climatology, 2017)
This study aimed at identification of abrupt change points ( CPs ) and detection of gradual trends in 34‐year (1980–2013) annual rainfall at nine stations of an Indian arid region. The CPs were determined by five tests and their significance was examined by two tests. Furthermore, trends were tested by three tests and their magnitudes were quantified by two tests. Novelty of the study lies in investigating significance of trends sequentially over years by applying Mann–Kendall (M–K) test. The identified CPs were similar for standard normal homogeneity test and cumulative deviations test at most stations. In contrast, Pettitt and Bayesian tests detected CP in years 2002 and 2005 at six and three stations, respectively, and their significance was verified. Results of sequential M–K test did not match with other tests' results. The mean annual rainfall after CP (350–627 mm) increased by 14–80% of the amount before CP (306–444 mm) with 7–42% reduction in coefficient of variation. The box–whisker plots supported these findings. Results of trend tests indicated statistically significant trends at Anjar, Bhachau, Mandvi and Rapar. Trend magnitudes by linear regression prior to CP (−6.2 to 7.1 mm year −1 ) showed an overall increase after CP (4.7–40.8 mm year −1 ) with negative trend at one station. Sen's slope test, showing good harmony with linear regression, revealed that trend magnitudes after CP were 2–10 times higher than that for 34‐year period at six stations. Results of M–K test applied for sequential periods emphasized that rainfall trends are becoming stronger over time. This finding suggests that significance level of increasing rainfall trends may further increase in future. Finally, findings of this study are useful for planners and decision makers for developing policies to meet the challenges of the heightened rainfall in study area. Also, the approach used here may be adopted in other parts of the globe.

Estimating Water Balance of Small Reservoirs in Arid Regions: A Case Study from Kachchh, India - Deepesh Machiwal; Devi Dayal; Sanjay Kumar (Agricultural Research, 2017)

Characterizing rainfall of hot arid region by using time-series modeling and sustainability approaches: a case study from Gujarat, India - Deepesh Machiwal; Sanjay Kumar; Devi Dayal (Theoretical and Applied Climatology, 2016)

Comparing GIS-based multi-criteria decision-making and Boolean logic modelling approaches for delineating groundwater recharge zones - Deepesh Machiwal; P. K. Singh (Arabian Journal of Geosciences, 2015)

Estimation of Soil Erosion and Identification of Critical Areas for Soil Conservation Measures using RS and GIS-based Universal Soil Loss Equation - Deepesh Machiwal; Pratibha Katara; H. K. Mittal (Agricultural Research, 2015)

Modeling Short-Term Spatial and Temporal Variability of Groundwater Level Using Geostatistics and GIS - Deepesh Machiwal; Amit Mishra; Madan K. Jha; Arun Sharma; S. S. Sisodia (Natural Resources Research, 2012)

Assessment of Groundwater Potential in a Semi-Arid Region of India Using Remote Sensing, GIS and MCDM Techniques - Deepesh Machiwal; Madan K. Jha; Bimal C. Mal (Water Resources Management, 2011)

GIS-based assessment and characterization of groundwater quality in a hard-rock hilly terrain of Western India - Deepesh Machiwal; Madan K. Jha; Bimal C. Mal (Environmental Monitoring and Assessment, 2011)

Estimation of Sediment Yield and Selection of Suitable Sites for Soil Conservation Measures in Ahar River Basin of Udaipur, Rajasthan using RS and GIS Techniques - Deepesh Machiwal; S. K. Srivastava; Sadhna Jain (Journal of the Indian Society of Remote Sensing, 2010)

Determination of hydraulic parameters of an unconfined alluvial aquifer by the floodwave-response technique - Madan K. Jha; K. Jayalekshmi; Deepesh Machiwal; Y. Kamii; K. Chikamori (Hydrogeology Journal, 2004)

Planning and Design of Cost-effective Water Harvesting Structures for Efficient Utilization of Scarce Water Resources in Semi-arid Regions of Rajasthan, India - Deepesh Machiwal; Madan K. Jha; P. K. Singh; S. C. Mahnot; A. Gupta (Water Resources Management, 2004)